Irradiation of subcutaneous mouse tumors with a clinical linear accelerator validated by alanine dosimetry. (September 2021) - Ankjærgaard, C.; Johansen, A.Z.; von Staffeldt, M.M.K.; Andersen, C.E.; Madsen, D.H.; Behrens, C.F.
Abstract: Preclinical radiotherapy studies using mouse models are an indispensable step on the path from in vitro experiments to clinical implementation. In support of this step, dedicated small animal irradiators have been developed to provide a platform for testing new radiation strategies for cancer treatment. Although some systems offer an advanced setup including high resolution positioning and imaging, the investment in obtaining, maintaining, and using small animal irradiators is substantial both monetary and in man-hours. An alternative approach is to use linear accelerators (LINACs) designed for irradiation of humans and widely available in clinical environments, as they may potentially increase quality and translational value of preclinical cancer research. Here we present a simple setup for fast and localized irradiation of subcutaneous mouse flank tumors using a clinical 10 MV flattening filter free (FFF) LINAC beam. Alanine pellet dosimeters were used for validation of the setup. Good agreement was found between alanine and the vertical Eclipse dose profile both outside and inside the field. Additionally, the alanine pellets verified the in vivo dose to the mouse tumor location by comparing and finding agreement between the dose from ten subcutaneously inserted dosimeters and ten externally placed dosimeters. Finally, the setup was tested using the syngeneic CT26 colon cancer mouse model. A single dose of 15 Gy was provided to subcutaneous tumors on the right flank. Comparison of tumor growth between the irradiated and non-irradiated tumors showed a delay in tumor growth and improved overall survival amongst the irradiated mice. This study demonstrates that clinical LINACs are an easy, fast, and cost effective alternative to small animal irradiators without compromising accurate dose delivery. Clinical LINACs could be utilized to a greater extent in preclinical studies. Highlights: Clinical linear accelerator used for irradiation of subcutaneous mouse flank tumors. The setup is easy to use and fast in delivery compared to small animal irradiators. The alanine dosimeter is a good representation of the in vivo dose to a mouse tumor.